Password Strengthening by Using Keystroke Dynamics - Teh, Pin Shen (2008)
In this thesis,we have proposed a promising method to strengthen existing password authentication system based on individuals\' typing pattern. Using keystroke dynamics as an additional biometric security entity is reliable, fast, non invasive and cost-effective. This additional security mechanism is invisible to users as they only need to type on a keyboard as usual and the security mechanism will be responsible to capture and process the users\' typing timing pattern without their knowledge.